Evaluation of toxic metals in natural fish populations in Oklahoma. - Farley, Perry Dwain (My University, 1981)
The level of toxic metals was low in the water samples but were much higher in the sediment samples. There were no significant correlations beween the levels of toxic metals in the water to the levels in the sediment.

A study was conducted to determine effects of arsenic, cadmium, chromium, copper, lead, and mercury on the natural fish populations in Oklahoma. Fish samples were collected annually at 23 monitoring stations for herbivore and carnivore trophic levels during Water Years (October 1 to September 30) 1977, 1978, 1979, and 1980.

Samples of the water column and sediment were also collected and analyzed for the same toxic metals as the fish samples. Additionally, pH, total hardness, and flow were analyzed at the monitoring stations. These measurements were taken to determine if they had an effect on the toxicity of the toxic metals analyzed to the natural fish populations.

The concentrations of toxic metals studied in the natural fish populations in Oklahoma were generally low and no observed patterns of elevated toxic metals in the fish samples could be determined. There were no direct correlations between the toxic metal levels in the water and sediment samples and the levels measured in the fish samples. No correlations were noted in the pH, total hardness, and flow measurements to the toxic metal levels in the fish samples. Since no patterns were observed in the fish data, it was not possible to predict the sources of these toxic metals.
Keywords: Chemistry, Biochemistry.